Pengaruh Gaya Kepemimpinan Situasional, Disiplin Kerja Dan Pengalaman Kerja Terhadap Prestasi Kerja Karyawan Hotel Fourpoints By Sheraton Medan - Sudrajad, Mifta; Darmilisani; Sebayang, Saimara AM (Journal of Community Research and Service, 2025)
The research analysis aims to find out whether situational leadership style partially has apositive and significant effect on the work performance of employees of the Fourpoints By SheratonMedan Hotel. Does work discipline partially have a positive and significant effect on the workperformance of Fourpoints By Sheraton Medan Hotel employees? Does partial work experiencehave a positive and significant effect on the work performance of Fourpoints By Sheraton MedanHotel employees. Whether situational leadership style, work discipline and work experiencesimultaneously have a positive and significant effect on the work performance of Fourpoints BySheraton Medan Hotel employees. The data analysis technique used is a quantitative researchmethod with the help of the SPSS program. This study uses multiple linear regression. The samplein this study was 42 respondents. Primary data collection uses questionnaires. The results of thestudy show that situational leadership style partially has a positive and significant effect on the workperformance of employees of the Fourpoints By Sheraton Hotel Medan. Work discipline partiallyhas a positive and significant effect on the work performance of Fourpoints By Sheraton MedanHotel employees. Work experience partially has a positive and significant effect on the workperformance of Fourpoints By Sheraton Medan Hotel employees. Situational leadership style, workdiscipline and work experience simultaneously have a positive and significant effect on the workperformance of Fourpoints By Sheraton Medan Hotel employees.